Modelling Of Graphene Based Multimode Interference Waveguide As A Refractive Index Optical Sensor - Yeoh, Stephenie (2022)
Over the recent years, demands for compact, portable, sensitive and easy to fabricate sensing devices have grown rapidly for industrial, medical and environmental applications. However, it remains a challenge to miniaturise the device while ensuring high sensitivity and efficient sensing in a wide range of wavelength. The state-of-the-art devices suffer from high losses and narrow detection range of analytes at the near-infrared (NIR) spectral regions. This research overcomes these issues by integrating graphene on a multimode interference (MMI) structure which is composed of a dielectric planar waveguide confined by a substrate and a cladding layer. The high refractive index (RI) of graphene layer of 2.345 causes the modes to be less confined in the core region. The enhancement of evanescent field on the surface of the waveguide results in higher sensitivity to changing RI in surrounding medium. The dispersion relation of transverse magnetic (TM) modes is derived from Maxwell’s equations to investigate the impact of the geometric and optical parameters including thickness, conductivity and refractive indices. Graphene is modelled as a homogeneous film with finite thickness to investigate the sensitivity of the effective refractive index